Geometry of design : studies in proportion and composition. - Elam, Kimberly, 1951- (New York : Princeton Architectural Press, 2001)
At last, a mathematical explanation of how art works presented in a manner we can all understand. Kimberly Elam takes the reader on a geometrical journey, lending insight and coherence to the design process by exploring the visual relationships that have foundations in mathematics as well as the essential qualities of life. Geometry of Design-the first book in our new Design Briefs Series-takes a close look at a broad range of twentieth-century examples of design, architecture, and illustration (from the Barcelona chair to the Musica Viva poster, from the Braun handblender to the Conico kettle), revealing underlying geometric structures in their compositions. Explanations and techniques of visual analysis make the inherent mathematical relationships evident and a must-have for anyone involved in graphic arts. The book focuses not only on the classic systems of proportioning, such as the golden section and root rectangles, but also on less well known proportioning systems such as the Fibonacci Series. Through detailed diagrams these geometric systems are brought to life giving an effective insight into the design process.
Includes bibliographical references (p. 104) and index.
Keywords: Art, Modern -- 20th century; Composition (Art).; Fibonacci numbers; Golden section; Proportion (Art).; Vormleer